Diagnosis and treatment of radiation damage - the acute radiation syndrome - Klutmann, Susanne (Radiology and oncology (Ljubljana), 1997)
Radiation mainly yields to a damage of highly reproductive cells, i.e. radiosensitive tissues like bone marrow, gastrointestinal mucosa, and hair follicles. With increasing doses radiation causes damage of more differentiated, i.e. relatively radioresistant organs like the central nervoussystem as well. The acute radiation syndrome presents with an uniform sequence of 3 phases: the prodromal stage with unspecific symptoms like vomiting and nausea, followed by a phase of subjective well-being, i.e. the latency phase. The thirs phase of the acute radiation syndrome has been divided into three major catagories: 1. bone marrow syndrome, 2. gastrointestinal syndrome, and 3. central nervous syndrome. Each syndrome is defined by dose, survival time, and symptoms. Survival of the patients is mainly limited by radiogenic damage to the bone marrow, and causal treatment like bone marrow transplantation may be successful after whole-body irradiation below 10 Gy. Whereas after applied doses above 10 Gy the therapeutic approach will predominantly be palliative preventing patients frompain and suffering.
Keywords: Diagnosis; Radiation injuries; Therapy